Poverty Approach and How to Reduce it with an Agropolitan Program in Gorontalo Province, Indonesia - Aulia Ika Rahmawati; Lutfi Ardianti; Salma Hayyu Nur Husna; Eni Paryani; Nur Amrina Rosidhah; Tiara Putri Amalia; Ratih Fitria Putri (ASEAN Journal on Science and Technology for Development, 2019)
This study aimed to explain the conditions of poverty in Gorontalo Province, Sulawesi, Indonesia, to identify the causes of poverty in the province, and then to propose efforts to reduce this poverty. Data related to human and economic resources were used in the analysis. The condition of poverty was seen through the DPSIR approach, which consists of the driver (D), pressure (P), state (S), impact (I), and response (R). Poverty in Gorontalo Province could be reduced by utilizing the occupation that dominates the population, which is in agriculture sector. Therefore, developing an agropolitan system is a solution. In the first stage, the location quotient (LQ), shift share (SS), and Klassen typology methods were used to determine regencies or cities that have the potential to develop an agropolitan system. The results of the analysis showed that there were two districts that have the potential to develop agropolitan systems, namely Pohuwato Regency and Gorontalo Regency. Efforts to reduce poverty in Gorontalo Province with an agropolitan system can be continued with a second stage consisting of the preparation of products and forms of management organizations, and a third stage in the form of strengthening human resources.